Failed States in International Relations - Čepilová, Barbora; Kváča, Vladimír, 1977-; Knotková, Vladimíra; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
The aim of the work Failed States in International Relations is the examination of this phenomenon regarding the terminological discrepancy, causes of the state fragility, security and social aspects and the various attitudes from the side of the international communities. A special part is dealing with so called "successfully failed states" where despite the obvious non-functioning the state is able to survive due to the revenues from the natural resources. The ?ndings are represented on the case study of the Democratic Republic of the Congo - a country with huge potential but miserable performance by now.
Vedoucí práce: Vladimír Kváča
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses